Gambaran Tingkat Pengetahuan tentang Kesehatan Reproduksi pada Remaja SMA di Kabupaten Kubu Raya - Nupus, Restu Hayatun; Ligita, Mita Titan (UPT Percetakan dan Penerbitan Universitas Jember, 2024)
Indonesian adolescent reproductive health mentions one of the actions of adolescents that often becomes a problem for their reproductive health is that adolescents have friends who have had sexual relations at the age of 15-19 years. Females accounted for 34.7%, and adolescent boys 30.9%. This condition shows that adolescents very highly carry out premarital sex behavior, and this sexual activity puts adolescents at risk of various reproductive health problems. This study aimed to determine the level of knowledge about reproductive health in high school adolescents in Kubu Raya Regency. The method in this study was carried out using a quantitative descriptive research design with a cross-sectional research approach. The sampling using a stratified random sampling technique. The results obtained were the categories of knowledge found in respondents, namely, knowledge level of knowledge amounted to 160 people (74.4%), medium amounted to 45 people (20.9%), and less amounted to 10 people (4.7%). Based on the research results, it was found that women found the level of knowledge by gender to be better than that of men.